Working in partnership with the Charitable Food Sector to Better meet the Food Needs of People in Perth - Pollard, Christina; Booth, Sue; Begley, Andrea; Kerr, Deborah; Jancey, Jonine (Council to Homeless Persons, 2016)
The Western Australian community faces increasing numbers of people vulnerable to food insecurity due to their economic or social circumstance. This is partly due to geographic isolation and the cost of food, as well as the demise of the mining boom and a stalled economy. For example, food costs more in remote areas, 26 per cent more for a healthy food basket than in the Perth metropolitan area. Welfare dependent families in WA would need to spend 44 per cent of their disposable income to purchase a healthy diet compared to only 14 per cent average income earners.1 This simply does not happen, as food is the one area families can sacrifice to pay for other expenditures